Synergized physical and technical training model for 12-13-year-old swimmers: benefits for annual training cycle - Arishin, A.; Pogrebnoy, A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test benefits of the new synergized physical and technical training service model for the 12-13-year-old swimmers within their annual training cycle.